PEMANFAATAN LAHAN DALAM PENGELOLAAN TANAMAN HIDROPONIK UNTUK MENINGKATKAN UMKM DI DESA CIDEHENG TENGAH - Gatot Hartoko; Venty Ramadhanty; Rahmawati Dewi; Suratmi Suratmi; Lastiur Situmorang; Jumaedi Jumaedi; Mutiara Aisyah Lubis (Yayasan Education and Social Center, 2021)
Hydroponics is also known as soilless culture or soilless plant cultivation. So, hydroponics can be interpreted as cultivating plants that utilize water and without using soil as a planting medium. The purpose of counseling activities to the community with the theme